All‐Earth‐Abundant Photothermal Silicon Platform for CO2 Catalysis with Nearly 100% Sunlight Harvesting Ability. Issue 2 (26th August 2020) - Zhang, Dake; Lv, Kangxiao; Li, Chaoran; Fang, Yaosi; Wang, Shenghua; Chen, Zhijie; Wu, Zhiyi; Guan, Wenhao; Lou, Deyue; Sun, Wei; Yang, Deren; He, Le; et al.
Abstract : Photothermal CO2 hydrogenation catalyzed by earth‐abundant materials, such as non‐noble metals, has emerged as an industrially viable and sustainable way of effectively converting solar energy into chemical energy stored in fuels and other valuable chemical feedstocks. However, the performance of existing non‐noble metal photocatalysts often suffers from incomplete sunlight utilization, limited photothermal effect, and poor stability under intense light illumination. Herein, the fabrication of all‐earth‐abundant on‐silicon architectures with nearly 100% sunlight harvesting ability is demonstrated. The cobalt‐loading‐optimized architecture exhibits a high photothermal CO2 conversion rate of 0.433 mol·gCo −1 ·h −1 . A spatial confinement strategy based on surface encapsulation with a thin layer of silica is further used to improve the stability of supported Co nanoparticles against sintering. This strategy of maximizing the sunlight absorbance of non‐noble metal photocatalysts lays a foundation for industrial implementation of all‐earth‐abundant photothermal CO2 catalysis. Abstract : An all‐earth‐abundant on‐silicon architecture with nearly 100% sunlight harvesting ability is developed for photothermal hydrogenation of carbon dioxide. The platform to maximize the sunlight absorbance of non‐noble photocatalysts lays a foundation for industrial implementation of all‐earth‐abundant photothermal CO2 catalysis.